Development of IoT-based agriculture monitoring framework using node-red - Foong, Theen Wui (2023)
In this era of globalization, the implementation of internet technology has been adapted in majority of the sectors. By adapting it in our daily task, it is making the execution process of our task more convenient and efficiently. Recently, the food security problem has become one of the main issues since the war that happening in some places and the limited amount of land for agriculture in the country. The production of the crops in our country is affected seriously and the peoples had to buy the vegetables with a higher price. Since agriculture sector is one of the main contributors to the GDPs of our country, we need to ensure its sustainability and making use of land by introducing the development of indoor farming with the integration with IoT.Thus, this project aims to build a IoT-based Agriculture Monitoring Framework that can receive the environment data and automate some of the processes of indoor farming. In this project, Raspberry Pi and Node-RED will be studied and used to build the framework. Since the environment of indoor farming are required to monitor by the user, few sensors will be attached with the Raspberry Pi so that the data such as temperature, humidity, water level and current value can be collected. The collected data will be stored in database and the user can access it through a dashboard. Furthermore, a chatbot will be created to ease the process of farm management for the user since it supports remote monitoring. In a nutshell, a framework will be built to ensure the crops can live in a suitable environment and makes the indoor farming activities more efficient.